(untitled) (Boston, 2004)
Classroom concepts will "come to life" with this outstanding fifth edition of "Life" by authors Lewis, Gaffin, Hoefnagels, and Parker. Ricki Lewis is well known for her ability to weave together solid biology content with interesting stories, real-life case studies and applications to student life. The fifth edition offers the depth of content, pedagogical organization, accuracy and visual appeal to serve both majors and non-majors biology students alike.
Keywords: Biology,Human biology